Comparison of the protective effects of ischemic preconditioning and the Na+ /H+ exchanger blockade - Mosca, Susana María (2000)
The protective effects of ischemic preconditioning (IP) and Na+/H+ exchanger blockade (NHEb) by two blockers [ethylisopropylamiloride (EIPA) and HOE 642] were compared in the isovolumic perfused rat heart. The impairment in systolic and diastolic function detected in control ischemic hearts (C) exposed to 20 min of ischemia and 30 min of reperfusion was diminished in similar extent by IP and by NHEb with EIPA and HOE 642. At the end of the reperfusion period +dP/dtmax values were 57±9% in C hearts and 94±6%, 82±6% and 104±6% after IP and NHEb with EIPA and HOE 642, respectively. A depletion of ATP levels detected in C hearts after reperfusion (from 20.2±0.8 µmol/g dry weight before ischemia to 6.9±0.7 µmol/g dry weight) was partially prevented by both IP and NHEb with EIPA (9.2±0.7 µmol/g dry weight and 11.1±0.5 µmol/g dry weight, respectively). The ischemic contracture (IC), assessed by the left ventricular end diastolic pressure (LVEDP), observed in C hearts (35±4 mmHg) was not decreased by IP (40±4 mmHg) but it was prevented by NHEb (18±4 mmHg and 10±3 mmHg with EIPA and HOE 642, respectively). The ATP levels at the end of the ischemic period were similar in C and IP hearts (4.1±0.2 µmol/g dry wt vs. 3.3±0.4 µmol/g dry wt) but they were significantly higher after NHEb with HOE 642 (7.0±1.0 µmol/g dry wt). PKC inhibition by chelerythrine abolished the protection induced by IP after reperfusion although not the improvement induced by NHEb with EIPA.